Wireless Ordering & Reservation System (WORS) / Lim Choon Siang - Lim , Choon Siang (2001)
Wireless Ordering & Reservation System or in short called WORS is a restaurant system which is based on the wireless environment. Most of the restaurants today are still using the old-fashion way of taking orders and reservation on a piece of paper. This kind of practice is very troublesome, inefficient and not systematic at all. By implementing WORS, customers will be able to make their reservation through their mobile phone whereas waiters and waitresses will be using wireless pocket PC for ordering process. In fact, this project is important in bringing the restaurant system to the new age to accomplish the growth of the "Wireless Technology". Besides, WORS will be able to keep track of all transaction into the database and generating the sales report in a period of time. In order to provide more efficient and better quality services, this project will be developing through several stages. Information was gathered on the development models and tools. Apart from that, research was done on the similar system to study the strengths and weaknesses of the current system. The Waterfall Model with Prototyping approach was chosen for the development of this project because the strengths of both the waterfall model and prototyping can be combined in a single project and reduces the risks involved. Software and technology selection are Microsoft Windows 2000 server, Microsoft Internet Information Service 5.0, Microsoft SQL server 2000, Wireless Markup Language (WML), WML script, Active Server Pages 3.0, Microsoft Visual Basic 6.0 and Microsoft eMbedded Visual Basic 3.0. And the system requirement of this WORS is the clientserver technology with three-tier technology. During the early stage, many problems were inevitably encountered due to the high degree of uncertainty in some area of user requirements, system requirements, complexity and unfamiliarity of setting up and configuration the servers. Finally, this project outcome will reflect the characteristics of information such as accuracy, reliability, timely and integrity.